DISPENSASI PEMBUKAAN LAHAN PERTANIAN SECARA DIBAKAR BERDASARKAN KEARIFAN LOKAL - Salfius Seko; Yanuar Rachmatul Ridha; Hadiryaman Laowo; Markus Peri Anggara; Ryanto Hartono; Sudarso (Ganesha Law Review, 2024)
This study aims to understand the practice of Land Opening Dispensation through Burning Based on the Local Wisdom of the Dayak Tobag community in West Kalimantan. In this context, the research seeks to comprehend the culture, values, and perspectives of the local community regarding land clearing through burning. The study's findings are expected to provide deeper insights into this practice, inform more inclusive policies and regulations, and formulate sustainable land management approaches. Thus, this research can make a significant contribution to environmental protection and the preservation of the Dayak Tobag community's culture while maintaining a balance between economic development and nature conservation.